Plants that express a potyvirus proteinase gene are resistant to virus infection. - Maiti, I B (1993)
Transgenic tobacco plants that express the genome-linked protein/proteinase-coding region of the potyvirus tobacco vein mottling virus (TVMV) were produced and tested for their reaction to inoculation with TVMV and two other potyviruses. These plants did not develop disease symptoms after being inoculated with large doses of TVMV but were as susceptible to infection by the other potyviruses as were control plants. Lines of tobacco that express the coat protein- or the nonstructural cylindrical inclusion protein-coding regions were also produced. The coat protein transgenic plants were protected against all three potyviruses, and the cylindrical inclusion transgenic plants were susceptible to all three potyviruses. These results indicate that some, but not all, TVMV genes can be used to confer protection against potyviruses in plants. The results also suggest that combinations of viral genes in transgenic plants might improve protection against potyviruses.